Conjugated Porphyrin Materials for Solar Fuel Generation - Bai, Yang; Sprick, Reiner S. (Current Organic Chemistry, 2022)
Conjugated materials have emerged as a new class of photocatalysts for solar fuel generation, thus allowing for the Sun’s energy to be converted into a storable fuel that can be used without further emissions at the point of use. Many different building blocks have been used to make conjugated materials that act as photocatalysts allowing for efficient light absorption and tuing of photophysical properties. The porphyrin moiety is a very interesting building block for photocatalysts as the large π-conjugated system allows efficient light absorption. Metalation of porphyrins allows for further tuning of the materials’ properties, thus further expanding the property space that these materials can cover. This allows to design and better control over the properties of the materials, which is discussed in this review together with the state-of-the-art in porphyrin photocatalysts and hybrid systems.
Keywords: conjugated materials